Absolute terahertz power measurement of a time-domain spectroscopy system - Globisch, Björn; Dietz, Roman J B; Göbel, Thorsten; Schell, Martin; Bohmeyer, Werner; Müller, Ralf; Steiger, Andreas (Optics letters, 2015)
We report on, to the best of our knowledge, the first absolute terahertz (THz) power measurement of a photoconductive emitter developed for time-domain spectroscopy (TDS). The broadband THz radiation emitted by a photoconductor optimized for the excitation with 1550-nm femtosecond pulses was measured by an ultrathin pyroelectric thin-film (UPTF) detector. We show that this detector has a spectrally flat transmission between 100 GHz and 5 THz due to special conductive electrodes on both sides of the UPTF. Its flat responsivity allows the calibration with a standard detector that is traceable to the International System of Units (SI) at the THz detector calibration facility of PTB. Absolute THz power in the range from below 1 μW to above 0.1 mW was measured.